Effect of a silvopastoral system with Leucaena diversifolia on enteric methane emissions, animal performance, and meat fatty acid profile of beef steers - Molina-Botero, Isabel Cristina; Villegas, Daniel M.; Montoya, Alejandro; Mazabel, Johanna; Bastidas, Mike; Ruden, Alejandro; Gaviria, Hernan; Peláez, Juan David; Chará, Julián; Murgueitio, Enrique; Moorby, Jon; Arango, Jacobo (Springer, 2024)
The aim of this research was to evaluate dietary inclusion of Leucaena diversifolia into a grass monoculture (GM) diet and its influence on enteric methane emissions, animal live weight gain and meat fatty acid content of steers. Two GM diets comprised Urochloa hybrid cv. Cayman or U. brizantha cv. Toledo; silvopastoral (SPS) mixed diets included an association of either grass with L. diversifolia in a 74:26 (grass:legume) planting ratio. The experiment was conducted over 16 months with 14 Brahman x Angus crossbred steers (374±7.5 kg body weight), divided into two diet groups. Steers were weighed periodically during the experiment, and methane emissions were quantified with the polytunnel technique. The meat quality and fatty acid profile were measured after slaughtering the steers. Energy density, total and digestible dry matter intake and crude protein were higher in steers fed SPS than GM ( P ≤0.05). At the end of the experiment, animals from SPS weighed on average 63 kg more than animals offered GM (535 vs. 472 kg; P =0.025). Net methane emitted by steers offered SPS was 142 g per day, this is equivalent to 15% less than emissions from animals that were offered GM (168 g; P =0.007). The meat fatty acid profile was similar between diets, except for cervoniv-DHA and omega-6: omega-3 ratio, which were higher in steers consuming GM diet ( P≤0.05 ). The results of this study suggest that the inclusion of L. diversifolia improves nutrient intake, increases animal productivity, reduces daily enteric methane emission, and decreases the omega-6: omega-3 ratio in meat.